2017
DOI: 10.1155/2017/3797802
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Factor Erythroid 2-Related Factor 2 in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is manifested as increased urinary protein level, decreased glomerular filtration rate, and final renal dysfunction. DN is the leading cause of end-stage renal disease worldwide and causes a huge societal healthcare burden. Since satisfied treatments are still limited, exploring new strategies for the treatment of this disease is urgently needed. Oxidative stress takes part in the initiation and development of DN. In addition, nuclear factor erythroid 2-related factor 2 (Nrf2) plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 139 publications
(166 reference statements)
0
32
0
Order By: Relevance
“…Its activation triggers a powerful antioxidant response by synthesizing more than 250 genes [290]. Oxidative stress is closely linked to inflammation in diabetes mellitus and DN [291]. Nrf2 activation ameliorates pancreatic cell damage and its suppression aggravates cellular death in diabetic mice [292].…”
Section: Nrf2mentioning
confidence: 99%
“…Its activation triggers a powerful antioxidant response by synthesizing more than 250 genes [290]. Oxidative stress is closely linked to inflammation in diabetes mellitus and DN [291]. Nrf2 activation ameliorates pancreatic cell damage and its suppression aggravates cellular death in diabetic mice [292].…”
Section: Nrf2mentioning
confidence: 99%
“…A phase II clinical trial using Baricitinib, a selective JAK-1 and JAK-2 inhibitor, showed a reduction of proteinuria and expression of several inflammatory markers in patients with DKD [85]. Nuclear factor-2 erythroid related factor (Nrf2)-keep 1 pathway has been also shown to play a major role in the progression of DKD [87]. Pharmacological activation of Nrf2 decreases cytokine production, M1 macrophage accumulation, and the formation of an atherosclerotic plaque lipid core in the experimental model of streptozotocin-induced diabetic mice on an apolipoprotein E-deficient background [88].…”
Section: Challenges and Opportunities In Developing New Therapies Formentioning
confidence: 99%
“…Therefore, the cellular antioxidant molecules try to abolish the harmful effect of ROS to maintain cellular integrity [ 5 ]. Oxidative stress-associated pathological processes can be attenuated by the nuclear factor-erythroid-2- (NF-E2-) related factor 2 (Nrf2) molecule that sustains cellular redox homeostasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%